The influence of institutional characteristics on implementing school-based universal addiction prevention: a Hungarian mixed-methods nationwide study on the state of implementation, barriers, and facilitators - Árva, Dorottya; Vokó, Zoltán; Sápi, Mária; Cselkó, Zsuzsa; Rákosy, Zsuzsa (Frontiers in Education, 2024)
Background: In Hungary, as in other European countries, substance and behavioral addictions are an increasing problem among children and adolescents. Schools play a vital role in providing the knowledge and skills needed to prevent addictions. However, various factors influence the overall effectiveness of such efforts. To design more effective preventive interventions, it is necessary to evaluate existing programs and identify possible points to intervene. Our aim was to assess the current state of addiction prevention in Hungarian schools, identify barriers, and explore facilitators that contribute to the successful implementation of addiction prevention. Methods: A nationwide cross-sectional survey-based quantitative study was performed to investigate the implementation of addiction prevention in Hungarian elementary schools (N=2892). With the participation of 37 teachers from 21 elementary schools, a focus group-based qualitative study was conducted to investigate teachers’ perspectives on such programs and ways to improve them. Results: Among the addiction topics, alcohol (61.9%), smoking (73.6%), and drug use (71.3%) were the most covered themes. Problematic use of the internet and electronic devices was addressed in 60.9% of the schools, while gaming and gambling were addressed in only 18.9%. Of schools, 55.1% reported having regular programs to support pupils’ mental health, and this differed significantly by school type and size. Logistic regression analysis revealed that the type of school, the support for teachers’ work, and the diversity of implementers were significantly associated with the quality of implementation of addiction prevention. The qualitative study showed that addiction prevention is hindered by inappropriate family or teacher models, increased workloads, and challenges in collaborating with colleagues and parents. According to the teachers, they can do the most for the health of children at school, but they need support for effective implementation. Conclusion: Our results indicate the importance of school characteristics in addiction prevention implementation and call for the support and empowerment of teachers and greater organizational capacity to ensure the effectiveness of school-based addiction prevention activities. By understanding these barriers and facilitators, policymakers and educators can develop evidence-based strategies to improve the effectiveness of prevention programs.